Prospek Pengembang an Usaha Tani Cabai Keriting (Capsicum annum, L) di Kebun Praktek Fakultas Pertanian Universitas Nusa Nipa Indonesia - Teofilus Mastaram; Gabriel Otan Apelabi (Jurnal Ilmiah Wahana Pendidikan, 2022)
Chili or lombok (Capsicum, L) is a seasonal vegetable horticultural plant for spices that is needed by all levels of society as a flavoring of cuisine and appetite enhancer. This research aims to find out to find out the prospects for the development of chili farming business in the planted practice of the faculty of agriculture, University of Nusa Nipa Indonesia. As for the results of the research obtained that: the prospects of chili farming development based on SWOT analysis are well developed, namely being on an aggressive strategy formed in quadrant 1, namely growth oriented strategic (supporting aggressive growth policies).